Here's the question you clicked on:
Sophmoregrad2014
how do you change standard form into vertex form
Typically you have to complete the square, then move the constant term to the left side with your y variable.
I'm assuming you're referring to the quadratic function here and not some other function with a vertex.
can you give me an example becuase its on my test tommorow and my teacher cant explain it
So lets say you have some quadratic equation in the form: \[y = x^2 + 2x -8\] To write it in vertex form, we need to have something like: \[y-y_1 = C(x-x_1)^2\] So we need to take the x^2 and the 2x and make something that is just (x-x1)^2. To do that, we take half of the coefficient on the x term and square that. So half of 2 is 1, 1 squared is 1. Then we simultaneously add and subtract (adding a 0) that amount out of the equation: \[\implies y = x^2 + 2x + 1 - 1\ - 8\] Then we collect out completed square: \[\implies y =(x-1)^2 - 1 -8\] Combine the constant parts: \[\implies y = (x-1)^2 - 9\] Then add or subtract the constant part to the other side: \[\implies y+9 = (x-1)^2\] That's vertex form and shows that the quadratic has a vertex at (1,-9)
change the parabola equadion from vertex form to standared form
i think that it because i suck and math
ok so if the equation is: \[3x ^{2} + 4x - 7\]